Đồng tạo giá trị và lòng trung thành của khách hàng thế hệ Z trong bối cảnh nền kinh tế số tại Việt Nam: Vai trò trung gian của trải nghiệm thương hiệu trực tuyến - Đỗ Anh , Đức; Trương Tuấn, Anh; Phạm Kiên, Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study examines the impact of value co-creation on Generation Z (Gen Z) customers' loyalty while also investigating the mediating role of online brand experience in the context of Vietnam's digital economy. The research employs a quantitative method using Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis of a sample of 426 Gen Z customers in Vietnam reveals that value co-creation positively influences Gen Z's loyalty in the context of Vietnam's digital economy. Additionally, online brand experience plays a mediating role in this relationship. The authors provide key insights and managerial recommendations for business leaders.
Keywords: Online brand experience; Digital economy; Gen Z’s loyalty; Value co-creation